Environmental impacts of polypropylene (PP) production and prospects of its recycling in the GCC region - Amzan Alsabri (17148397) (2022)
Undoubtedly, plastic products are widely used by nearly everyone, either in plastic bags, bottles, household items, and many others. Hence, plastic products are replacing almost all other items, and as a result, they are causing environmental hazards as well. Polypropylene (PP) is a common plastic used to create end goods for customers, such as plastic packaging, and it accounts for 16 % of the entire plastics industry. The Gulf Cooperation Council (GCC) has emerged as a global exporter of petrochemical products, including chemicals, consumer care products, pharmaceuticals, automobiles, textiles, and agricultural products in the past few years. This has led to the growing demand for PP production and raises the environmental concerns associated with PP waste. In this work, the life cycle assessment (LCA) studies are consolidated to analyze the environmental impacts related to PP production and waste. Furthermore, several options of utilizing plastic waste have been presented and discussed from the environmental perspectives and for the GCC region. Other Information Published in: Materials Today: Proceedings License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matpr.2021.11.574